2014
DOI: 10.1093/cercor/bht427
|View full text |Cite
|
Sign up to set email alerts
|

Convergent BOLD and Beta-Band Activity in Superior Temporal Sulcus and Frontolimbic Circuitry Underpins Human Emotion Cognition

Abstract: The processing of social information in the human brain is widely distributed neuroanatomically and finely orchestrated over time. However, a detailed account of the spatiotemporal organization of these key neural underpinnings of human social cognition remains to be elucidated. Here, we applied functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) in the same participants to investigate spatial and temporal neural patterns evoked by viewing videos of facial muscle configurations. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…To this end, previous functional neuroimaging research has shown distinct neural pathways involved in the perception of emotion from static and dynamic facial expressions (i.e., Kilts et al, 2003 ). Consistent with these findings, results from Jabbi et al ( 2015 ) suggest that oscillatory activity in the beta frequency band may track dynamic changes in sensory input facilitating the differentiation of emotional expressions. Although the use of dynamic facial expressions adds an additional level of stimulus complexity, it also affords greater ecological validity, which can improve our understanding of the neural dynamics underpinning naturalistic emotion perception.…”
Section: Future Directionssupporting
confidence: 54%
See 1 more Smart Citation
“…To this end, previous functional neuroimaging research has shown distinct neural pathways involved in the perception of emotion from static and dynamic facial expressions (i.e., Kilts et al, 2003 ). Consistent with these findings, results from Jabbi et al ( 2015 ) suggest that oscillatory activity in the beta frequency band may track dynamic changes in sensory input facilitating the differentiation of emotional expressions. Although the use of dynamic facial expressions adds an additional level of stimulus complexity, it also affords greater ecological validity, which can improve our understanding of the neural dynamics underpinning naturalistic emotion perception.…”
Section: Future Directionssupporting
confidence: 54%
“…Given the importance of beta oscillations in the perception of biological motion, which is thought to be critical for social cognition in naturalistic environments (Pavlova, 2012 ). Jabbi et al ( 2015 ) used MEG to compare evoked beta band activity in response to dynamic and static facial expressions. Perhaps unsurprisingly, greater beta power was observed for dynamic compared to static facial expressions in occipital, superior temporal and sensorimotor cortices.…”
Section: Perception Of Emotion From Facial Expressionsmentioning
confidence: 99%
“…Previous research has demonstrated that EEG beta activity is related to emotional and cognitive processes 47 , which reflects on the craving aspect of alcoholism. Also, in an fMRI and MEG study, researchers found convergent BOLD and beta-band activity in the fronto-limbic circuitry that underpins emotional cognitive processes 48 . Based on these previous findings, our result of convergent BOLD and beta-band activity in pgACC and dACC can strongly support that these cortical areas have an important role in processing emotional and cognitive aspect in alcoholism, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, current discussions address whether the relationship between the BOLD response and neuronal signal, neurovascular coupling is underspecified ( Bentley et al, 2016 ; Conner et al, 2011 ; Jabbi et al, 2015 ; Nir et al, 2007 ) and could be more complex. For example, uncoupling between CBV increase and power change in high-frequency LFP was observed in experimental animals ( Huo et al, 2014 ) for reasons that are still not fully clear.…”
Section: Introductionmentioning
confidence: 99%